2020
DOI: 10.2147/oaem.s241501
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cyclosporine-A-Based Immunosuppressive Therapy-Induced Neurotoxicity: A Case Report</p>

Abstract: Cyclosporine-A (CsA) and mycophenolate mofetil are immunosuppressive drugs used for the prevention of transplant rejection. Various clinical studies have been performed on different forms of CsA neurotoxicity, including tremor, paresthesia, confusion, ataxia, neuralgia, hemiplegia, occipital seizures, and transient cortical blindness. Mycophenolate is associated with several neurological side effects including headache, insomnia, dizziness, depression, confusion, hypertonia, and paresthesia. A 31-year-old male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…(2) cyclosporine and tacrolimus, used in the kidney and liver transplant population; in addition to cerebellar ataxia, these drugs can also cause tremor, paresthesias, or even seizures, encephalopathy, and cognitive dysfunction [104][105][106][107] ; (3) metronidazole, an antibiotic for anaerobic coverage, can cause bilateral dentate hyperintensity on T2 FLAIR as the classic imaging finding, which can be reversible after drug discontinuation 108,109 ; (4) irinotecan and cytarabine, chemotherapy agents used to treat colorectal cancer 110,111 and acute myeloid leukemia, respectively; high doses of either medication can result in irreversible cerebellar atrophy and persistent ataxia followed by an acute phase 101 ; postmortem examination reveals cerebellar Purkinje cell loss despite normal imaging, suggesting toxicity to Purkinje cells 112 ;…”
Section: Drug-induced Ataxiamentioning
confidence: 99%
See 1 more Smart Citation
“…(2) cyclosporine and tacrolimus, used in the kidney and liver transplant population; in addition to cerebellar ataxia, these drugs can also cause tremor, paresthesias, or even seizures, encephalopathy, and cognitive dysfunction [104][105][106][107] ; (3) metronidazole, an antibiotic for anaerobic coverage, can cause bilateral dentate hyperintensity on T2 FLAIR as the classic imaging finding, which can be reversible after drug discontinuation 108,109 ; (4) irinotecan and cytarabine, chemotherapy agents used to treat colorectal cancer 110,111 and acute myeloid leukemia, respectively; high doses of either medication can result in irreversible cerebellar atrophy and persistent ataxia followed by an acute phase 101 ; postmortem examination reveals cerebellar Purkinje cell loss despite normal imaging, suggesting toxicity to Purkinje cells 112 ;…”
Section: Drug-induced Ataxiamentioning
confidence: 99%
“…While complete recovery is expected after discontinuation of such drugs, some, especially lithium, are associated with chronic cerebellar ataxia, suggesting irreversible damage. 101 The common offending agents associated with cerebellar ataxia are: (1) amiodarone, commonly used for atrial fibrillation, cerebellar ataxia, and bilateral vestibulopathy are typical symptoms for amiodarone-induced ataxia 102 103 ; (2) cyclosporine and tacrolimus, used in the kidney and liver transplant population; in addition to cerebellar ataxia, these drugs can also cause tremor, paresthesias, or even seizures, encephalopathy, and cognitive dysfunction 104 105 106 107 ; (3) metronidazole, an antibiotic for anaerobic coverage, can cause bilateral dentate hyperintensity on T2 FLAIR as the classic imaging finding, which can be reversible after drug discontinuation 108 109 ; (4) irinotecan and cytarabine, chemotherapy agents used to treat colorectal cancer 110 111 and acute myeloid leukemia, respectively; high doses of either medication can result in irreversible cerebellar atrophy and persistent ataxia followed by an acute phase 101 ; postmortem examination reveals cerebellar Purkinje cell loss despite normal imaging, suggesting toxicity to Purkinje cells 112 ; (5) lithium, a mood stabilizer; lithium-induced cerebellar ataxia should be particularly considered in the setting of impaired renal function, active infection, and dehydration. Lithium may still induce cerebellar ataxia, despite being in a “therapeutic range.” 113 Thus, the diagnosis of lithium-induced ataxia should be based on clinical symptoms, such as nausea, vomiting, tremor, and myoclonus associated with ataxia, as well as the temporal relationship between the drug initiation and symptom development.…”
Section: Drug-induced Ataxiamentioning
confidence: 99%
“…Commonly used immunosuppressive drugs for the prevention of transplant rejection are tacrolimus, CsA, and mycophenolate mofetil [ 114 ]. CsA does not suppress bone marrow and its potential side effects include nephrotoxicity, hypertension, gingival hyperplasia, hypertrichosis, infection, hyperkaliemia, hypomagnesaemia, hepatotoxicity, increased incidence of specific tumors, and neurotoxicity [ 115 , 116 , 117 ].…”
Section: Pharmacological Classes Involved In Cardiotoxicity and Neuro...mentioning
confidence: 99%
“…Regarding mycophenolate mofetil, it can cause neurological side effects such as headache, insomnia, dizziness, depression, confusion, hypertonia, and paresthesia [ 119 ]. Computed tomography scanning and magnetic resonance imaging represent the main tools for evaluating radiological abnormalities in patients with CsA-induced neurotoxicity [ 120 ], such as signal changes in the cerebral cortex and juxta-cortical white matter of the occipital lobes, temporal, parietal, and frontal lobes [ 114 ].…”
Section: Pharmacological Classes Involved In Cardiotoxicity and Neuro...mentioning
confidence: 99%
“…Nevertheless, it has several side effects. For instance, a recent study demonstrated that up to 50% of patients have CsA-associated neurotoxicity in both intravenous and oral administrations which makes the CsA mechanism of action remain ambiguous [ 5 ].…”
Section: Introductionmentioning
confidence: 99%